Association between the VDR Ff polymorphism, muscle strength and a national athlete status - Park, D.; Kim, C.; Lee, S. (Archivos de medicina del deporte, 2008)
Background: Bone mineral density (BMD) is under strong genetic control and the genetic difference among individuals partly explains variance in adaptive response to exercise through gene-environment interaction. It has been demonstrated that skeletal muscle is a target organ for vitamin D and vitamin D defi ciency is associated with muscle weakness. Muscle strength is considered to be an important predictor of BMD and also, is one of most important factors to determine elite athlete performance. Purpose: The aim of this study was to determine whether the vitamin D receptor (VDR) gene polymorphism affected muscle strength in general population (CON) and was related with athlete performance in a national athlete (NA) status. Method: The VDR genotypes, as detected by endonuclease Fok I, bone phenotypes of the calcaneus, grip and back strength were examined in 409 general people (male n= 193, female n=218). The VDR genotype of 540 national athletes (male n= 339, female n= 201) was also determined. Results: No signifi cant association was found between the VDR genotypes and the BMD related variables (T-score, BUA and SOS) at the calcaneus, although there was a trend for an association between VDR genotypes (FF & Ff > ff) and BMD at the calcaneus in CON. However, the female subjects in CON with the VDR FF (40.5±13.4) and Ff (41.3±14.0) genotypes had a greater grip strength than the female subjects with ff genotype (34.6±13.8), respectively (p<.05, p<.05) while the male subjects with the VDR FF (74.0±19.3) and Ff (73.0±16.6) genotypes had a tendency for greater grip strength than the male subjects with ff genotype (69.2±23.3). In the back strength, there was no signifi cant difference between genotypes even though there was a tendency for greater back strength in male and female subjects with FF (67.6±47.3, 46.1±26.1) and Ff (68.6±47.7, 44.3±25.2) genotypes than male and female subjects with ff genotype (56.7±43.1, 34.5±28.9). In addition, we determined there to be a statistically signifi cant difference the genotypic frequency of VDR-FF, Ff, and ff between the general people (n=409, 33.9%, 49.4 %, and 16.7%) and a national elite athletes (n= 540, 40.0 %, 46.5 %, and 13.5 %; p=.037). Conclusions: According to our results, we concluded that genetic variation in the VDR is correlated with grip muscle strength in females and athletes with the VDR-FF and Fs genotypes might harbor a distinct advantage over athletes with the ff genotype.